The regulation reform for New Zealand financial advisers - Su, R; Xu, M; Dutta, A (AUT University, 2011)
The recent global financial crisis has highlighted the need to re-examine the connections between financial markets, institutions and their regulations. The New Zealand Government had passed the Financial Service Providers (Registration and Dispute Resolution) Act and the Financial Advisers Act into law in 2008. Under the new legislation regime, only AFAs (Authorised Financial Advisers) can provide wide range financial service after 1st July 2011. This article will go through the process of change and the details of new legislation of AFA; and provide the picture of New Zealand financial adviser regulation reform.